Economic impact of refugees - Taylor, J. Edward; Filipski, Mateusz J.; Alloush, Mohamad; Gupta, Anubhab; Rojas Valdes, Ruben Irvin; Gonzalez-Estrada, Ernesto (Proceedings of the National Academy of Sciences, 2016)
The number of refugees displaced by civil conflict or natural disasters is on the rise. Economic impacts of refugees on host countries are controversial and little understood, because data have not been available and the question of refugee impacts does not lend itself to conventional impact evaluation methods. We use a unique Monte Carlo simulation approach with microdata from refugee and host-country surveys to obtain the first estimates of refugee camps’ impacts on surrounding host-country economies and to compare impacts of cash versus in-kind refugee aid. An additional refugee increases total real income within a 10-km radius around two cash camps by significantly more than the aid the refugee receives. Impacts around a camp receiving in-kind (food) aid are smaller.